Are consumers willing to trade off sensory quality for health benefits? Experimental evidence from low glycemic index rice - Custodio, Marie Claire; Ynion, Jhoanne; Buenafe, Reuben James; Sreenivasulu, Nese; Demont, Matty; De Steur, Hans (Elsevier, 2025)
Diet-related non-communicable diseases (NCDs) disproportionately affect low- and middle-income countries, including Asia where milled rice is consumed as a staple food. Efforts to reduce NCD risks include the development of low glycemic index (GI) rice. However, the firmer texture associated with low-GI rice may hinder uptake in market segments where softer texture is preferred, such as in Southeast Asia. Little is known about consumers' valuation of low-GI rice and the tradeoff between health benefits and sensory quality. Since low-GI rice is a credence attribute, consumers need to be informed about its potential health benefits and this needs to be framed in the broader context of a healthy lifestyle. To understand this tradeoff, we conduct experimental auctions with 400 urban consumers in the Philippines to elicit sensory evaluation and willingness to pay (WTP) for low-GI rice and analyze the role of information and other factors through a double hurdle model. Compared with premium white rice as the benchmark, low-GI rice fetches lower sensory scores and is discounted by US¢13/kg. Healthy lifestyle information boosts WTP by US¢6/kg. WTP is positively associated with knowledge on Diabetes Type 2 and negatively with perceptions on the role of physical activity in preventing NCDs, underscoring the importance of communicating the complementary role of healthy eating and physical activity. These findings offer insights into key message framing in nutrition education programs and trait requirements for breeding programs to alleviate NCD risks through low-GI rice tailored to consumer requirements in the Global South.